2020
DOI: 10.18087/cardio.2020.3.n561
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of different assesment methods of myocardial fibrosis in patients with hypertrophic cardiomyopathy.

Abstract: Objective To evaluate prospects for clinical use of circulating biomarkers for characterizing fibrotic changes in the myocardium of patients with hypertrophic cardiomyopathy (HCMP) with left ventricular (LV) outflow tract obstruction.Materials and Methods This was a prospective study with a 12-month follow-up period. The study included 47 patients (29 females and 18 males) with obstructive HCMP who were selected for septal reduction. Echocardiography (EchoCG), cardiac magnetic resonance imaging (MRI) and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…On the one hand, there have been studies on DCM, HCM, and patients with CAD that showed correlations between galectin-3 and MMP-9 with LGE [ 30 , 31 , 32 ]. Conversely, studies on HCM, which explored TGF-β1; MMP-2 and MMP-9; TIMP-1; galectin-3; sST2; CITP, PICP, and PIIINP; hypertensive HF with PICP, PIIINP, CITP and MMP-1; valvular diseases (MMP-2, TIMP-1); and acute myocardial infraction populations (sST2) have reported a lack of any relationship between the biomarkers under analysis and LGE [ 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there have been studies on DCM, HCM, and patients with CAD that showed correlations between galectin-3 and MMP-9 with LGE [ 30 , 31 , 32 ]. Conversely, studies on HCM, which explored TGF-β1; MMP-2 and MMP-9; TIMP-1; galectin-3; sST2; CITP, PICP, and PIIINP; hypertensive HF with PICP, PIIINP, CITP and MMP-1; valvular diseases (MMP-2, TIMP-1); and acute myocardial infraction populations (sST2) have reported a lack of any relationship between the biomarkers under analysis and LGE [ 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…В литературе на текущий момент представлены немногочисленные исследования, посвященные изучению данного маркера обмена экстрацеллюлярного матрикса при СНпФВ в основном в рамках метаанализов рандомизированных клинических исследований [25]. Учитывая неоднозначные данные о диагностической значимости PICP в зависимости от этиологии СН, сопутствующих заболеваний, влияющих на метаболизм коллагена, выявленные различия в концентрациях описываемого биомаркера по результатам нашего исследования требуют дальнейшего изучения [26,27].…”
Section: Discussionunclassified
“…У всех участников было подтверждено повышение уровней MMP-2, -9, ТИМП-1, Gal-3, sST2, CITP, PICP, PIIINP, транс формирующего фактора роста-β1. Однако корреляции между уровнем биомаркеров и степенью фиброза по данным морфометрического анализа интраоперационных биоптатов миокарда и МРТ сердца не выявлено [49]. В 2020г Vullaganti S, et al стремились связать наличие замещающего фиброза, измеряемого методом ПНГ, и диффузного фиброза, измеряемого по внеклеточному объему коллагена с помощью МРТ, с выявленными ВНП в генах саркомерных белков.…”
Section: биомаркеры фиброзаunclassified